Multi-objective optimization of cloud manufacturing service composition with cloud-entropy enhanced genetic algorithm - Li, Yongxiang (Strojniški vestnik, 2016)
To consider the service-matching degree, the composition harmony degree, and the service composition complexity in cloud manufacturing service composition optimization problems, a new composition optimization approach, called cloud-entropy enhanced genetic algorithm (CEGA), is put forward to solve such problems with multi-objectives. The definitions of service-matching degree, composition harmony degree, and cloud-entropy and the corresponding calculation methods are given. A multi-objective optimization mathematical model of cloud manufacturing service composition is built. The manufacturing task of AGV (automated guided vehicle) is taken as an example to verify the proposed CEGA algorithm on the established composition model. The studied result shows that CEGA converges faster than a standard genetic algorithm with shorter time.
Keywords: entropija oblaka; genetski algoritem; optimizacija sestave storitev; proizvodnja v oblaku; stopnja harmonije sestave; stopnja primernosti storitev